Application of ZnO Nanoparticles for Improving the Thermal and pH Stability of Crude Cellulase Obtained from Aspergillus fumigatus AA001 - Srivastava, Neha; Srivastava, Manish; Mishra, P. K.; Ramteke, Pramod W. (Frontiers in Microbiology, 2016)
Cellulases are the enzymes which are responsible for the hydrolysis of cellulosic biomass. In this study thermal and pH stability of crude cellulase has been investigated in the presence of zinc oxide (ZnO) nanoparticles. We synthesized ZnO nanoparticle by sol-gel method and characterized through various techniques including, X-ray Diffraction (XRD), ultraviolet-visible spectroscope (UV-Vis), field emission scanning electron microscope (FE-SEM) and high resolution scanning electron microscope (HR-TEM). The crude thermostable cellulase has been obtained from the Aspergillus fumigatus AA001 and treated with ZnO nanoparticle which shows thermal stability at 65oC up to 10 h whereas it showed pH stability in the alkaline pH range and retained its 53% of relative activity at pH 10.5. These findings may be promising in the area of biofuels production.